2005
DOI: 10.1079/pavsnnr20051001
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on information requirements for import and release of invertebrate biological control agents in European countries.

Abstract: Several international documents have been published in recent years with the objective of providing guidance to industry, biocontrol practitioners and competent national regulatory authoritieson the regulatory framework for the import and release of invertebrate biological control agents(IBCAs). As the scope and the level of detail given in these documents were diverse in many respects, it has been difficult for all stakeholders to apply such guidelines, and to integrate them in a harmonized way into national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 0 publications
0
47
0
4
Order By: Relevance
“…Accurate identification of insect parasitoids used (or being considered for use) in biological control programs is a fundamental step in assessing their suitability and performance (Bigler et al 2005;Greenstone 2006). The taxon-specific multiplex-PCRs developed in the present study provide means by which any life stage of the major members of the complex of parasitoids attacking soft scales in California citrus groves (Lampson and Morse 1992;Bernal et al 2001;Kapranas et al 2007) can be accurately and rapidly identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate identification of insect parasitoids used (or being considered for use) in biological control programs is a fundamental step in assessing their suitability and performance (Bigler et al 2005;Greenstone 2006). The taxon-specific multiplex-PCRs developed in the present study provide means by which any life stage of the major members of the complex of parasitoids attacking soft scales in California citrus groves (Lampson and Morse 1992;Bernal et al 2001;Kapranas et al 2007) can be accurately and rapidly identified.…”
Section: Discussionmentioning
confidence: 99%
“…A critical step in assessing an organism's potential for biological control is the ability to accurately identify it (Bigler et al 2005). This can be problematic if definitive morphological characters are elusive or difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…The simple fact that regulation concerning import and release of exotic natural enemies does not exist in some countries and is not well organized in other countries has resulted in this problematic situation . As a result, the topic of implementation of a registration procedure for natural enemies is currently hotly debated by the biological control industry, scientists and regulators (Blum et al 2003;GreatRex 2003;van Lenteren et al 2003van Lenteren et al , 2006aAnonymous 2004;Bigler et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Current activities in the field of regulation will hopefully result in a light and harmonized registration procedure that is not prohibitive for the biological control industry and will result in the pre-selection of safe natural enemies (see e.g. Bigler et al 2005). A proposed quick scan method for organisms already in use (van Lenteren and Loomans 2006) should be considered as a kick-start from a situation with no regulations for the use of biological control agents, to one where import and release are regulated to ensure safe use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation